Apoptosis in kidney tissue is activated in an early period after radiofrequency ablation - Kinčius, Marius; Preidis, Andrius; Dambrauskas, Žilvinas; Gulbinas, Antanas (Lietuvos chirurgija, 2016)
ObjectiveHyperthermia induced apoptosis may lead to tumor cell death thus expanding the volume of non-viable tissue and warrant a “safety margin” of at least 10mm to exclude the possibility of tumor recurrence. We carried out an experimental study to investigate the cellular injury produced by radiofrequency ablation in the area surrounding the ablated tissue and to describe early apoptotic processes in the transition zone following radiofrequency ablation procedure in a porcine kidney model.Materials and methodsEight anesthetized pigs underwent laparotomy and local thermal ablation of the kidney parenchyma. The ablated tissue and the surrounding parenchyma were investigated for apoptosis applying Western blot analysis and immunohistochemistry.ResultsThe active (cleaved) caspase-3 17-kDa subunit was detected in the transition zone one hour after ablative procedure at a distance of 7-9 mm from the rim of the necrosis zone. In contrast analysis of tissues in necrosis zone and in surrounding normal kidney parenchyma revealed no markers of apoptotic activity.ConclusionsWe determined that apoptosis, leading to further cell death, is activated in the majority of cells in the transition zone, thus supporting the hypothesis that the “safety margin” of 8 mm is encompassed by the indirect thermal effect.
Keywords: kidney cancer; radiofrequency ablation; apoptosis; caspase-3